2008
DOI: 10.1016/j.jacc.2008.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound Imaging of Intraplaque Neovascularization in Carotid Arteries

Abstract: Carotid plaque contrast-agent enhancement with sonographic agents correlates with histological density of neovessels and is associated with plaque echolucency, a well-accepted marker of high risk lesions, but it is unrelated to the degree of stenosis. Contrast-enhanced carotid ultrasound imaging may provide valuable information for plaque risk stratification and for assessing the response to antiatherosclerotic therapies, beyond that provided by standard ultrasound imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
219
1
29

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 305 publications
(263 citation statements)
references
References 39 publications
12
219
1
29
Order By: Relevance
“…Many efforts have been recently made using non-invasive techniques [8][9][10][11][12] for identifying plaques at high risk of disruption leading to thrombosis, generally defined as "vulnerable plaques" [13,14]. These latter lesions are characterized by a large necrotic core with an overlying thin cap rich in inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been recently made using non-invasive techniques [8][9][10][11][12] for identifying plaques at high risk of disruption leading to thrombosis, generally defined as "vulnerable plaques" [13,14]. These latter lesions are characterized by a large necrotic core with an overlying thin cap rich in inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al (35) identified a strong correlation between CEUS analysis of plaque neovascularization in carotid arteries and histological scores on surgical specimens. Coli et al (39) demonstrated that CEUS measurements of contrast enhancement correlated well with histologically determined neovessel density in plaques.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is interesting because carotid plaque neovascularization has also been evaluated by contrast-enhanced sonography and has recently been regarded as a surrogate marker of atherosclerosis due to associations with plaque echolucency and ischemic symptoms. [20][21][22] Comparing findings of neovascularization between contrast-enhanced ultrasonography and OCT would be important in future examinations.…”
Section: Discussionmentioning
confidence: 99%